(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
R. K. Narayan is narrowed down to the south, then a tiny village-like town but now a major area, Malgudi. The city now stands halfway between various ancient and superstitious beliefs and culture on the one side and glamour and appeal of the new beliefs and living standards on the other. The present essay discusses the topics of modernity and marginality, the endless tension between the traditional and the new, the ancient and contemporary spirit, and the orthodox and liberal approaches to social lives and problems in Malgudi, based on the novels by Narayan. His novels portray an Indian macrocosm of religions, values and society.